1977
DOI: 10.1021/bi00635a022
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of ethidium bromide fluorescence enhancement on binding to nucleic acids

Abstract: The mechanism of the enhancement of the fluorescence of ethidium bromide on binding to double helical RNA and DNA has been investigated. From an examination of the effect of different solvents on the fluorescence lifetime, quenching of fluorescence by proton acceptors, and the substantial lengthening of lifetime observed upon deuteration of the amino protons, regardless of the medium, we conclude that proton transfer from the excited singlet state is the process primarily responsible for the approximately equa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
284
3

Year Published

1983
1983
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 528 publications
(322 citation statements)
references
References 43 publications
27
284
3
Order By: Relevance
“…Spectrally resolved FLIM Q. S. Hanley S85 dequenching process similar to EB (Olmsted & Kearns 1977;Jones et al 1978;Leupin et al 1985). These data (figure 2) were originally published as plots of phase and modulation lifetime spectra.…”
Section: Ab-plotsmentioning
confidence: 99%
“…Spectrally resolved FLIM Q. S. Hanley S85 dequenching process similar to EB (Olmsted & Kearns 1977;Jones et al 1978;Leupin et al 1985). These data (figure 2) were originally published as plots of phase and modulation lifetime spectra.…”
Section: Ab-plotsmentioning
confidence: 99%
“…an alcohol, whereas the fluorescence emission wavelength does not vary appreciably. This behaviour cannot be explained satisfactorily in terms of normal solvent-induced reordering in the excited state [20]. However, it is accounted for in the analysis of LeBret and Chalvet [23] by specific interactions between solvent molecules and the phenanthridiniuin ring.…”
Section: Poly[d(g-c)] (----) and Poly[d(a-t)] Po[y(d(a-t/] ()mentioning
confidence: 98%
“…For ethidium bromide bound to calf thymus DNA the enhancement has been reported to be around 20 [3] or 12 [20], under different experimental conditions.…”
Section: Poly[d(g-c)] (----) and Poly[d(a-t)] Po[y(d(a-t/] ()mentioning
confidence: 99%
See 1 more Smart Citation
“…Among the many different mechanisms proposed to explain this enhancement, the intercalation of ethidium bromide into DNA is the most plausible one. 27,32 More recently, the fluorescence spectra of 4-[4-(dimethylamino)styryl]-1-dodecyl pyridinium bromide (DMASDPB) mixed with DNA-CTMA were studied by Grote et al 24 As shown in Figure 6, the film containing the lowest level of dye presented the greatest fluorescence intensity. Compartmentalization of the dye molecules in the DNA-CTMA matrix must be the reason for this observation.…”
Section: Fluorescence Of Dye-doped Dnasmentioning
confidence: 99%